The impact of protocluster environments at z = 1.6 - Hatch, Nina A.; Cooke, Elizabeth A.; Muldrew, Stuart I.; Hartley, William G.; Almaini, O.; Conselice, Christopher J.; Simpson, C.J. (Oxford University Press, 2016)
We investigate the effects of dense environments on galaxy evolution by examining how the properties of galaxies in the z = 1.6 protocluster Cl 0218.3−0510 depend on their location. We determine galaxy properties using spectral energy distribution fitting to 14-band photometry, including data at three wavelengths that tightly bracket the Balmer and 4000 Å breaks of the protocluster galaxies. We find that two-thirds of the protocluster galaxies, which lie between several compact groups, are indistinguishable from field galaxies. The other third, which reside within the groups, differ significantly from the intergroup galaxies in both colour and specific star formation rate. We find that the fraction of red galaxies within the massive protocluster groups is twice that of the intergroup region. These excess red galaxies are due to enhanced fractions of both passive galaxies (1.7 times that of the intergroup region) and dusty star-forming galaxies (3 times that of the intergroup region). We infer that some protocluster galaxies are processed in the groups before the cluster collapses. These processes act to suppress star formation and change the mode of star formation from unobscured to obscured.